2010
DOI: 10.1090/s0002-9939-10-10288-3
|View full text |Cite
|
Sign up to set email alerts
|

The weak Lefschetz property and powers of linear forms in 𝕂[𝕩,𝕪,𝕫]

Abstract: Abstract. We show that an Artinian quotient of an ideal I ⊆ K[x, y, z] generated by powers of linear forms has the Weak Lefschetz Property. If the syzygy bundle of I is semistable, the property follows from results of Brenner-Kaid. Our proof works without this hypothesis, which typically does not hold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 8 publications
(18 reference statements)
0
40
0
Order By: Relevance
“…Results of Harima, Migliore, Nagel and Watanabe [13] show that WLP always holds for r 2. For r = 3, WLP holds for ideals of general forms [2], complete intersections [13], ideals with semistable syzygy bundle and certain splitting type, and almost complete intersections with unstable syzygy bundle [3], certain monomial ideals [18] and ideals generated by powers of linear forms [21]. The following example of Migliore-Miró-Roig-Nagel [18] shows that the result of Schenck and Seceleanu [21] can fail for r 4, and motivates this paper.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Results of Harima, Migliore, Nagel and Watanabe [13] show that WLP always holds for r 2. For r = 3, WLP holds for ideals of general forms [2], complete intersections [13], ideals with semistable syzygy bundle and certain splitting type, and almost complete intersections with unstable syzygy bundle [3], certain monomial ideals [18] and ideals generated by powers of linear forms [21]. The following example of Migliore-Miró-Roig-Nagel [18] shows that the result of Schenck and Seceleanu [21] can fail for r 4, and motivates this paper.…”
Section: Introductionmentioning
confidence: 69%
“…This is surprising: for I ⊆ K[x 1 , x 2 , x 3 , x 4 ] generated by general forms, Migliore and Miró-Roig show in [16] that the quotient ring always has WLP. It also contrasts to most known cases of powers of linear forms: WLP always holds in the three-variable case [21] and for complete intersections (that is, r = n). The result on complete intersections is due to Stanley [22], who showed that if I = l t1 1 , .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…1 has maximal rank for all i, s. When this property holds, the algebra is said to have the strong Lefschetz property (briefly SLP). In [14], Schenck and Seceleanu gave the nice result that any artinian ideal I ⊂ R = k[x, y, z] generated by powers of linear forms has the WLP. Moreover, when these linear forms are general, the SLP of R/I has also been studied, in particular, the multiplication by the square ℓ 2 of a general linear form ℓ induces a homomorphism of maximal rank in any graded component of R/I, see [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…If d = 4, then D = 0, by Proposition 3.2. With the notations as in the case 2, one has L 11 (11; 914 ) = dim[R 6,3 ] 11 if d = 5 dim k L 11 (10; 8 14 ) = dim[R 6,3 ] 10 if d = 7 dim k L 11 (9; 7 14 ) = dim[R 6,3 ] 9 if d = 9.…”
mentioning
confidence: 99%